2000
DOI: 10.1046/j.1365-2044.2000.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, anaesthesia and Guillain Barré syndrome

Abstract: SummaryTwo case histories of pregnant women with Guillain Barre  syndrome (acute demyelinating polyradiculoneuritis) are reported. The ®rst required anaesthesia during the second trimester for a minor surgical procedure. The second woman was admitted to the Intensive Care Unit in the ®rst trimester and was ventilated for 18 weeks. Both babies were carried to term and delivered by Caesarean section. A review of the management of Guillain Barre  syndrome in pregnancy discusses anaesthetic management, intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 17 publications
0
42
1
5
Order By: Relevance
“…The management of GBS in pregnancy is similar to that in the non-pregnant population 7 and includes intravenous (i.v.) immunoglobulins and plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…The management of GBS in pregnancy is similar to that in the non-pregnant population 7 and includes intravenous (i.v.) immunoglobulins and plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Feldman reported that a parturient with Guillain-Barré syndrome had a cardiac arrest due to hyperkalemia that occurred shortly after succinylcholine administration for general anaesthesia 6 . Non-depolarizing muscle relaxants should be administered with caution, because they may result in prolonged neuromuscular block and postoperative mechanical or assisted ventilation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…También existen varios casos de resultados favorables después de la anestesia regional 8,18---20 y no hay evidencias de que la anestesia regional pueda desencadenar la enfermedad 16 . Por tanto, el SGB no debe ser considerado una contraindicación absoluta para la realización de anestesias en el neuroeje 8,9,18 . Existe un aumento de la sensibilidad a los anestésicos locales, por tanto la dosis debe ser reducida y siempre que se pueda fraccionada, con el fin de evitar los bloqueos extensos 15 .…”
Section: Discussionunclassified